Pengaruh Solvabilitas, Profitabilitas dan Aktivitas Terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi pada Perusahaan Sektor Energi di BEI Periode 2020-2024 - Prasetyo, Edo Bagus; Elfiswandi, Elfiswandi; Pratiwi, Hanna (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the effect of solvency, profitability, and activity on company value with company size as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange during the period 2020–2024. This study uses a quantitative approach with an explanatory research method. The sample was determined using purposive sampling, resulting in 26 companies with a total of 130 observation units. The research data was analysed using panel data regression analysis with a moderated regression analysis (MRA) approach. The results showed that solvency did not have a significant effect on company value, while profitability and activity had a significant effect on company value. Furthermore, company size was found to moderate the effect of solvency and profitability on company value, but did not moderate the effect of activity on company value. These findings indicate that financial performance, particularly profitability and the effectiveness of company activities, plays an important role in increasing company value, with company size serving as a factor that strengthens certain relationships.